Dhiya Az Zahra Umrah Management System - Yazid, Adib Nawfal; Sulaiman, Rabatul Aduni (Applied Information Technology And Computer Science, 2025)
Dhiya Az Zahra is a company specializing in Umrah services, but the current process relies on WhatsApp, Telegram, and Email for communication, leading to inefficient operations and disorganized customer registrations. The project objectives involve designing the Dhiya Az Zahra Umrah Management System using object-oriented approach, developing the Dhiya Az Zahra Umrah Management System using a web-based approach, and testing the developed Dhiya Az Zahra Umrah Management System using system testing and user acceptance testing. The project uses iterative methodology as the software development lifecycle model. After system deployment, customers can make Umrah reservation, and administrators and staff can manage customer data through web browsers. The project completion should result in a web-based system for the Dhiya Az Zahra Umrah Management System that can assist in the Umrah reservation process and ensure efficient data management for Dhiya Az Zahra.